Utilization of Interactive Multimedia Android-Based Archiving Towards Learning Independence - Dirgatama, Chairul Huda Atma; Ningharjanti, Patni; Indrawati, C. Dyah Sulisyaningrum; Wirawan, Arif Wahyu (Department of Economics Education, Faculty of Economics, Universitas Negeri Semarang, 2021)
This research aims to find out the use of interactive multimedia archiving based on android and its effect on the learning independence of vocational learners. Research is a type of research and development (R & D). Research methods using experiments are pretend experiments (Quaisy experiment). The research was conducted at Vocational High School Surakarta City in April-June 2021. The population in this study is all students of class X Vocational High School Surakarta school year 2020/2021. The sample used was 1 control class and 1 randomly selected experimental class. All treatment will be given to the same control class and experimental class except on the use of interactive multimedia archival based on android. Interactive multimedia android-based archival was successfully applied in the learning of class X OTKP. There is a significant difference in the increase in learning independence between experimental classes that use interactive multimedia android-based archival and control classes that do not use interactive multimedia android-based archival in the archival learning class X OTKP in Vocational High School Surakarta City school year 2020/2021. Interactive multimedia android-based archiving can be used as one of the alternative learning media that can be used to increase the independence of learning learners.